VIOLENCE AGAINST WOMEN IN THE 21st CENTURY TELESCOPE (Law and world, 2020)
The Equal Protection Clause was created to address and eliminate discriminatory practices and has been utilized to champion equality primarily in the areas of race, religion, ethnicity, gender and sexual preference. Judiciary is empowered with the authority to identify and determine when certain conduct, behavior and activity are considered to be illegal and constitutionally impermissible. For the court system to be effective, it is necessary for those individuals who are experiencing discrimination to report discriminatory practices to the appropriate authorities.